Gouty Tophi Mimicking Synovial Sarcoma of the Knee Joint - Haseeb AMBER; Vivek Ajit SINGH; Mansor AZURA (Archives of Rheumatology, 2012)
Deposition of tophi is a common complication of chronic gout; however, symptoms are not always well pronounced. In this article, we report an unusual case of intraarticular gouty tophi of the knee joint presenting as a locked knee and radiologically mimicking a synovial sarcoma. To our knowledge, gouty tophus causing such a complication (fixed flexion deformity) has not been reported. This case report serves to bring about awareness of an extraordinary presentation of gout, which in severe forms can mimic intraarticular tumors and bring about such a deformity.